The Variability of Crop Production in Private and Socialized Agriculture: Evidence from Eastern Europe - Brada, Josef C. (Journal of Political Economy, 1986)
The hypothesis that crop production is more variable under socialism than under capitalism because of systemic differences between incentives and the structure of property rights in private and socialized farms is tested in two ways. The first test compares the variability of output for seven crops in five eastern European countries for a period when agriculture was private with a period when it was socialized. The second test compares the variability of output in state, collective, and private farms within each country. These tests confirm that socialization of agriculture increases the variability of crop output and that the source of this increased variability is not greater fluctuations in yields but rather in the acreage devoted to individual crops.